Anxiety and depression in patients after surgery for head and neck cancer in Japan. Issue 3 (6th October 2015) - Suzuki, Miho; Deno, Minako; Myers, Mie; Asakage, Takahiro; Takahashi, Koji; Saito, Kenichi; Mori, Yoshiyuki; Saito, Hiroto; Ichikawa, Yuji; Yamamoto-Mitani, Noriko; Miyashita, Mitsunori
Abstract: Objective: The present study sought to examine the impact of physical symptoms, facial disfigurement, adequacy of preoperative information, and social support on anxiety and depression in Japanese patients with head and neck cancer (HNC) who had undergone surgery. Method: A cross-sectional study with 194 patients was conducted using a self-administered questionnaire. This instruments included the Hospital Anxiety and Depression Scale (HADS), the European Organization for Research and Treatment of Cancer (EORTC) Head and Neck cancer module (QLQ–H&N35), and a Social Support Scale developed by Okabayashi et al. (1997). Results: The majority (56.7%) had surgery two or more years before completing the questionnaire. More than 25% of respondents showed anxiety or depression. Higher levels of perceived social support were associated with lower rates of anxiety and depression ( p < 0.01). Sensory problems were associated with anxiety, and reduced sexuality was associated with depression ( p < 0.01). Perceived disfigurement and adequacy of preoperative information were not associated with anxiety or depression. Significance of Results: Survivors of HNC experience anxiety and depression for an extended period of time. Social support may alleviate the severity of these disorders. More research is needed to confirm the impact of facial disfigurement and that of the preoperative information provided by surgeons on psychological distress in HNC patients.